Comparison of three methods of feeding sows in gestation and the subsequent effects on lactation performance - Young, M.G.; Aherne, F.X.; Main, R.G.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 684 sows from breeding groups over six weeks were used to compare three methods of feeding during gestation and to assess the subsequent effects on lactation performance. Control gilts and sows were fed according to body condition based on a scale of 1 to 5, (1=thin, 5=fat). Sows were visually assessed for body condition at breeding and were assigned a daily feed allowance to achieve a body condition score of 3 at farrowing. Sow body condition was evaluated every two weeks throughout gestation, and feed allowance was adjusted as required. Treatment two used feeding levels based on backfat thickness (measured between d 0 and 5 after breeding) and weight at weaning for sows or weight at service for gilts. Feed allowance was calculated to achieve a target backfat of 19 mm at farrowing. Sow feeding level remained constant from d 0 to 101 of gestation. Feed allowances were based on modeled calculations of energy and nutrient requirements to achieve target sow maternal weight and backfat gain. Treatment three was identical to treatment two except that feeding pattern was altered for thin sows and gilts (<15 mm at service) in an attempt to reach 19 mm by d 36 of gestation. Sows were weighed at the previous weaning and gilts at-service and again between d 112 and 114 of gestation. Backfat was measured between d 0 and 5 and again between d 108 and 113 of gestation. Sows on treatments two and three achieved backfat of 19 and 19.1 mm at farrowing, respectively, while control sows numerically tended to have greater backfat at farrowing (20 mm). On average, sows targeted to gain large amounts (6 to 9 mm) of backfat in gestation failed to achieve target gains regardless of feeding method. Feeding sows in gestation based on backfat (treatments two and three) resulted in a higher proportion of sows in the target backfat range of 17 to 21 mm at farrowing and a lower percentage of fat sows (>21 mm) but no difference in the percentage of thin sows (<17 mm) compared to the standard method of feeding based on body condition. Gestation feeding method had no effect on performance during lactation. Feed intake in lactation was lower for high backfat sows (>21 mm) at farrowing compared to sows with <21 mm. The high proportion of sows in the optimum backfat category demonstrates that feeding based on backfat and body weight has potential for facilitating more precise gestation feeding.
Keywords: Sows; Backfat; Body condition score; swine